MODEL INOVASI PENGEMBANGAN DAN PENGENDALIAN MUTU PEMBELAJARAN KEMUHAMMADIYAHAN - Yulianis, Yulianis; Syutri, Halimah; Syakban, Ismail (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This article examines innovation models for the development and quality control of Kemuhammadiyahan learning in Muhammadiyah educational institutions. The study aims to formulate a systematic and integrative model that not only focuses on learning innovation but also ensures sustainable quality assurance. This research employs a qualitative descriptive approach through literature review, document analysis, and synthesis of Muhammadiyah educational policies and Islamic education quality management theories. The findings indicate that effective quality development and control of Kemuhammadiyahan learning require an integrated model consisting of curriculum innovation, pedagogical innovation, digital learning support, and continuous quality control mechanisms. The quality assurance cycle—planning, implementation, evaluation, and continuous improvement—serves as a strategic framework to maintain the relevance and effectiveness of Kemuhammadiyahan learning. Thus, innovation and quality control are inseparable processes in strengthening the values of progressive Islam (Islam Berkemajuan) within Muhammadiyah education.Keywords: Innovation Model; Quality Control; Kemuhammadiyahan Learning; Muhammadiyah Education; Islamic Education